Monitoring changes in forestry and seasonal snow using surface albedo during 1982–2016 as an indicator - T. Manninen; T. Aalto; T. Markkanen; M. Peltoniemi; K. Böttcher; S. Metsämäki; K. Anttila; P. Pirinen; A. Leppänen; A. N. Arslan (Biogeosciences, 2019)
The surface albedo time series, CLARA-A2 SAL, was used to study trends in the snowmelt start and end dates, the melting season length and the albedo value preceding the melt onset in Finland during 1982–2016. In addition, the melt onset from the JSBACH land surface model was compared with the timing of green-up estimated from Moderate Resolution Imaging Spectroradiometer (MODIS) data. Moreover, the melt onset was compared with the timing of the greening up based on MODIS data. Similarly, the end of snowmelt timing predicted by JSBACH was compared with the melt-off dates based on the Finnish Meteorological Institute (FMI) operational in situ measurements and the Fractional Snow Cover (FSC) time-series product provided by the EU FP7 CryoLand project. It was found that the snowmelt date estimated using the 20 % threshold of the albedo range during the melting period corresponded well to the melt estimate of the permanent snow layer. The longest period, during which the ground is continuously half or more covered by snow, defines the permanent snow layer (Solantie et al., 1996). The greening up followed within 5–13 days the date when the albedo reached the 1 % threshold of the albedo dynamic range during the melting period. The time difference between greening up and complete snowmelt was smaller in mountainous areas than in coastal areas. In two northern vegetation map areas (Northern Karelia–Kainuu and Southwestern Lapland), a clear trend towards earlier snowmelt onset (5–6 days per decade) and increasing melting season length (6–7 days per decade) was observed. In the forested part of northern Finland, a clear decreasing trend in albedo (2 %–3 % per decade in absolute albedo percentage) before the start of the melt onset was observed. The decreasing albedo trend was found to be due to the increased stem volume.